"Sabaka" = The hindu - Ferrin, Frank; Marcel, Nino; Karloff, Boris, 1887-1969; Frank Ferrin Productions; Cinetel Films ([Hollywood, CA] : Frank Ferrin Productions, 1954)
Gunga Ram, a young elephant trainer, swears vengeance on the killers of his sister Indria and her husband on the orders of the religious fire-cult leaders, the High Priestess and Ashok. The Maharajah of Bakore disbelieves him and Gunga Ram is also opposed by the Maharajah's General Pollegar. Gunga Ram sets out to expose and destroy the fire shrine of Sabaka. --
Nino Marcel, Boris Karloff, Lou Krugman, Reginald Denny, Victor Joy, June Foray.
Photography, Alan Stensvold, Jack McCoskey; editors, Jack Foley, John M. Foley; music, Daksnamurti.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 7, 2015)
Keywords: Action and adventure films; Internet videos; Streaming video